Thermal food processing : new technologies and quality issues - Sun, Da-Wen. (Boca Raton, FL : CRC Press, 2012)
'The challenge of maintaining both quality and safety in the thermal processing of foods results from the degradation of heat-sensitive quality attributes during processing. The editor of Thermal Food Processing: New Technologies and Quality Issues presents a comprehensive reference through authors that assist in meeting this challenge by explaining the latest developments and analyzing the latest trends in thermal food processing research and development. The book is divided into three parts for easy reference. Part I, Modeling of Thermal Food Processes, discusses the thermal physical properties of foods, recent developments in heat and mass transfer, innovative modeling techniques including artificial neural network modeling, and computational fuel dynamics. Part II, Quality and Safety of Thermally Processed Food, provides the latest research and development information used to maintain high quality and safety standards for certain types of food products including thermally processed meat, poultry, fishery products, dairy products, canned foods, and vegetables. Part III, Innovations in Thermal Food Processes, details existing, alternative thermal processing technologies, outlining their potential, future application in the food industry. These innovations include the ohmic heating technique, radio frequency energies, infrared rays, the combination of pressure and pH with thermal processing, and time-temperature integrators used in evaluating and controlling thermal processes'--
'Preface Thermal processing is one of the most important processes in the food industry. The concept of thermal processing is based on heating foods for a certain length of time at a certain temperature. The challenge of developing advanced thermal processing for the food industry is continuing in line with the demand for enhanced food safety and quality as associated with thermal processing is always some undesirable degradation of heat-sensitive quality attributes. The first edition of this book was published in 2006, with the aim of providing a comprehensive review of the latest developments in thermal food processing technologies, of stressing topics vital to the food industry today, of pinpointing the trends in future research and development, and of assembling essential, authoritative, and complete references and data that can be used by the researcher in the university and research institution or can serve as a valuable reference source for undergraduate and postgraduate studies. This will continue to be the purpose of this second edition. In the second edition, besides updating or rewriting individual chapters with the latest developments in each topic area, five new chapters have been added in order to enhance the contents of the book. In Part I, two new chapters, Thermal Effects in Food Microbiology and Modeling Thermal Microbial Inactivation Kinetics, have been added to provide fundamental knowledge of the related food safety issues raised in subsequent chapters. In Part II, a new chapter, Thermal Processing of Fruits and Fruit Juices, has been added to provide a complete coverage of thermally processed food products'--
Includes bibliographical references and index.
Keywords: Food -- Storage; Food -- Preservation